Development of Ball Launcher Training Devices for Drill Smash, Block, Passing in Volleyball Sports (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Achievement sports are carried out through a planned, graded, and sustained coaching and development process with the support of sports science and technology. The aims of this study were to: (1) produce a ball launcher training device design for drill smash, block and passing in volleyball; (2) Analyzing the effectiveness of ball throwing training devices for drill smash, block and passing in volleyball; (3) Analyzing the acceptance of ball launcher training devices for drill smash, block and passing in volleyball. This research used development research. The development technique used covers 10 steps, including; potential and problems, data collection, product design, design validation, usage test, product revision, trial, design revision, product revision, mass production. The data analysis technique in this study used descriptive percentages. The outcomes of this study resulted in a ball launcher devices for drill smash, block and passing in volleyball. Test the effectiveness of small-scale group items with an average overall score of